A simple and fast technique for radiofrequency-assisted perforation of the atrial septum in congenital heart disease - Juan Pablo Sandoval; Rajiv R Chaturvedi (Wolters Kluwer Medknow Publications, 2016)
Radiofrequency (RF) assisted perforation of the atrial septum was performed successfully in three infants using a 0.035΂ RF wire deployed through a Williams right posterior catheter. Balloon atrial septoplasty was performed over the 0.035΂ RF wire in two of them, shortening the procedural time.